Association of Maternal Prepregnancy Weight with Offspring Adiposity Throughout Adulthood over 37 Years of Follow‐up. Issue 1 (25th November 2018) - Schoppa, Isabelle; Lyass, Asya; Heard‐Costa, Nancy; de Ferranti, Sarah D.; Fox, Caroline; Gillman, Matthew W.; D'Agostino, Ralph; Levy, Daniel; Mendelson, Michael M.
Abstract : Objective: This study aimed to determine the relation of maternal prepregnancy weight with offspring BMI across adulthood from almost 40 years of follow‐up. Methods: BMI was measured in Framingham Heart Study Offspring cohort participants between 1971 and 2008. The association of maternal prepregnancy weight category (ascertained via direct measure and questionnaire) with serial offspring BMI, overweight, obesity, and change in BMI over time was tested, adjusted for age, sex, and a BMI genetic risk score; secondary models additionally adjusted for physical activity, dietary factors, smoking, education, and familial relatedness. Results: Among 863 participants at initial assessment (83 exposed and 780 controls), mean (SD) age was 33 (10) years, 53% were female, and mean BMI was 24.5 (4.1) kg/m 2 . Exposed offspring BMI was higher at every examination cycle, ranging from 1.5 (0.5) to 3.0 (0.5) kg/m 2 ( P < 0.001), with larger differences at later assessments. The rate of increase in offspring BMI over time was higher in exposed offspring before the age of 50 years (β [SE] = 0.07 [0.02] kg/m 2 per year; P = 0.004) but not after the age of 50 years (−0.05 [0.04] kg/m 2 per year; P = 0.2). Conclusions: Maternal prepregnancy weight is associated with greater offspring BMI throughout adulthood, with more rapid weight acceleration in early and midadulthood.